(untitled) (Salud, Arte y Cuidado, 2026)
Proper management of the water trap for pleural drainage in thoracic trauma is essential. This study aimed to evaluate the usefulness of using a non-sterile water trap for pleural drainage in thoracic trauma patients at the “Servicio de Cirugía de Tórax del Servicio Autónomo Hospital Universitario de Maracaibo”. Fifty-six patients of both sexes, aged 18 to 85 years, diagnosed with thoracic trauma were studied. The most common complications were hemothorax and pneumothorax, and less frequently, hemopneumothorax and diaphragmatic hernia. Only two patients (3.6%) presented with an insertion site infection, neither of whom received antibiotics. It is concluded that non-sterile water traps can be safely used in patients with thoracic trauma, and it is recommended that these patients receive antibiotic therapy with cephalosporins.